Cloned measles virus-specific T lymphocytes from a twin with multiple sclerosis. - Richert, J R (1983)
A measles virus-specific T lymphocyte clone derived from a measles-responder twin with multiple sclerosis has been produced. The cloned cells proliferate in response to measles virus but not mumps, vaccinia, or canine distemper viruses. The clone recognizes an antigen that is distributed in both the membrane and cytoplasmic fractions of cells infected with measles virus. Antigen is presented to the clone equally well by irradiated mononuclear cells obtained from the autologous subject and from her healthy, measles-nonresponder, HLA-identical twin. Studies with a panel of HLA-typed irradiated mononuclear cells indicate that antigen is presented to the clone in the context of a gene product linked to, but not identical with, HLA-DRw2. The clone produces interleukin 2 and has surface determinants recognized by OKT-3, OKT-4, and anti-HLA-DR monoclonal antibodies, but not by OKT-8. It thus appears to belong to the helper/inducer subpopulation of T lymphocytes.